2015
DOI: 10.1002/ejic.201500760
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Alkoxide Complexes as Catalysts for the Synthesis of Cyclic Carbonates from Carbon Dioxide and Epoxides

Abstract: Titanium alkoxides can catalyze efficient and selective synthesis of cyclic carbonates through CO2 insertion into epoxides when tetrabutylammonium bromide or iodide is used as a cocatalyst. Of the series of synthesized titanium alkoxides, the most active catalyst was one bearing an aliphatic bidentate alkoxide ligand, and it produced propylene carbonate under benign conditions (100 °C, 15 bar CO2, 3 h) with turnover frequencies of up to 116 h–1. The effect of reaction parameters such as pressure, temperature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 42 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…The NHC-Ti catalytic systems show very limited activity in the coupling of PO (TOF = 7-15 h −1 ) or SO (TOF = 2-7 h −1 ) with CO 2 in comparison to other titanium complexes: titanocene, 50,51 Cp(tetrazole) TiCl 2 , 52 (tetrazole)TiCl 3 (THF), (tetrazole) 2 TiCl 2 , 52 (bis-salphen) (TiCl 2 ) 2 31 and Ti-alkoxides. 53 In the previous study on CO 2 /CHO copolymerization catalyzed by monomeric NHC-Ti(IV) complexes, 29 it was shown that bulky ionic cocatalysts such as [PPN]Cl salts were important for the selective formation of PCHC. A similar trend was observed here and all complexes exclusively promote formation of completely alternated PCHC (≥99%) (runs 1-2 and 3-5, Table 1), supporting our assertion that a nucleophilic anion with bulky countercation is required for the NHC-Ti systems.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…The NHC-Ti catalytic systems show very limited activity in the coupling of PO (TOF = 7-15 h −1 ) or SO (TOF = 2-7 h −1 ) with CO 2 in comparison to other titanium complexes: titanocene, 50,51 Cp(tetrazole) TiCl 2 , 52 (tetrazole)TiCl 3 (THF), (tetrazole) 2 TiCl 2 , 52 (bis-salphen) (TiCl 2 ) 2 31 and Ti-alkoxides. 53 In the previous study on CO 2 /CHO copolymerization catalyzed by monomeric NHC-Ti(IV) complexes, 29 it was shown that bulky ionic cocatalysts such as [PPN]Cl salts were important for the selective formation of PCHC. A similar trend was observed here and all complexes exclusively promote formation of completely alternated PCHC (≥99%) (runs 1-2 and 3-5, Table 1), supporting our assertion that a nucleophilic anion with bulky countercation is required for the NHC-Ti systems.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…[71][72][73][74][75][76][77][78] Whilst a range of catalysts are known, those based on zinc showed particular promise and there is also recent precedent for titanium complexes showing activity. 79 Therefore, it was of interest to investigate heterodinuclear titanium-zinc catalysts for the alternating copolymerization.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that compound 2 exhibits outstanding catalytic activity for sulfur oxidation with 99% conversion for dibenzothiophene (DBT) into dibenzothiophene sulfone (DBTO 2 ) at 55 °C. Moreover, catalyst 2 also showed appealing catalytic activity in the CO 2 cycloaddition reaction, [34][35][36][37] with carbon dioxide as the reaction material transforming into cyclic carbonate, which may not only provide an economical and green reaction path to use in environmental protection, but also confirm that 2 can be used as a bifunctional material with great promise.…”
Section: Introductionmentioning
confidence: 93%